'Written in these scars are the stories I can't explain': A content analysis of pro-ana and thinspiration image sharing on Instagram. (March 2018) - Ging, Debbie; Garvey, Sarah
Since pro-anorexia websites began to appear in the 1990s, there has been a growing body of academic work on pro-ana and thinspiration communities online. Underpinned by a range of (inter)disciplinary perspectives, most of this work focuses on websites and blogs. There is a dearth of research and, in particular, gender-aware research on pro-ana practices and discourses in the context of newer mobile social platforms such as Instagram. Using a dataset of 7560 images, this study employs content analysis to ask whether, to what extent and how pro-ana identities and discourses manifest themselves on a more open, image-based platform such as Instagram. We demonstrate that, by mainstreaming pro-ana, Instagram has rendered visible pro-ana sensibilities such as abstinence and self-discipline in the broader context of distressed girls' lives and Western culture more generally. We conclude that this increased visibility may in fact be a positive development.